Purely absorptive fifth-order three-dimensional electronic spectroscopy - Zhang, Zhengyang (2013)
We demonstrate a method to measure a purely absorptive fifth-order three-dimensional (3D) electronic spectrum based on a pulse-shaper assisted pump-probe beam geometry setup. The 3D spectra are measured as a function of two independently controlled population times. With phase-cycling and data processing, purely absorptive 3D spectra of chlorophyll a are obtained.